Multiply first equaton by -1 and add to first
-2x+y=7
<u>4x-y=-4 +</u>
2x+0y=3
2x=3
divide 2
x=3/2
sub
2x-y=-7
2(3/2)-y=-7
3-y=-7
minus 3
-y=-10
negative 1 times both sides
y=10
(3/2,10)
(1.5,10)
B is ansre
Answer:
x=27
Step-by-step explanation:
(2x-18)+(4x)=180 bc its a straight line
simplify
6x-18=180
-18 -18
6x=162
divide
x=27
Answer:
1/x+5
Step-by-step explanation:
1. Rewrite 3x as a difference
x-2/x^2 + 5x-2 - 10
2. Factor out x from the equation, then factor out -2.
x-2/ x+(x+5) - 2(x+5)
3. Factor out x+5 from the expression
x-2/ (x+5)(x-2)
4. Reduce the fraction with x-2
x-2 / (x+5) x-2
1/x+5
Answer:
Angles FVE, FVD, and EVD have V as a vertex
Step-by-step explanation:
If V is the vertex of an angle, it's the point of that angle. So, it wants every angle you can make where V is the point of it.
It’s A!! hope that helped